Characteristics and Challenges of Dietary Supplement Databases Derived from Label Information. (3rd August 2018) - Saldanha, Leila G; Dwyer, Johanna T; Bailen, Richard A; Andrews, Karen W; Betz, Joseph W; Chang, Hua F; Costello, Rebecca B; Ershow, Abby G; Goshorn, Jeanne; Hardy, Constance J; Coates, Paul M
Abstract: Launched in 2008, the Dietary Supplement Label Database (DSLD) permits the search of any term that appears anywhere on product labels. Since then, the database's search and download features have been periodically improved to enhance use for researchers and consumers. In this review, we describe how to customize searches and identify products and ingredients of interest to users in the DSLD, and provide the limitations of working with information derived from dietary supplement product labels. This article describes how data derived from information printed on product labels are entered and organized in the DSLD. Among the challenges are determining the chemical forms, types of extract, and amounts of dietary ingredients, especially when these are components of proprietary blends. The FDA announced new dietary supplement labeling regulations in May 2016. The 2017 DSLD has been updated to reflect them. These new regulations and examples cited in this article refer to this redesigned version of the DSLD. Search selection characteristics such as for product type and intended user group are as described in FDA guidance and regulations for dietary supplements. For this reason, some age groups (such as teens and seniors) and marketing recommendations for use (e.g., weight loss, performance, and other disease- or condition-specific claims) are not included in the search selections. The DSLD user interface features will be revised periodically to reflect regulatory and technologic developments to enhance user experience. A comprehensive database derived from analytically verified data on composition would be preferable to label data, but is not feasible for technical, logistic, and financial reasons. Therefore, a database derived from information printed on product labels is the only practical option at present for researchers, clinicians, and consumers interested in the composition of these products.